Manajemen Supervisi Akademik dalam Pembelajaran: Strategi dan Implementasi - Muaripin, Muaripin; Muaripin, Ary Maulana (JURNAL SYNTAX IMPERATIF : Jurnal Ilmu Sosial dan Pendidikan, 2024)
Academic supervision is an important aspect of education management that aims to improve the quality of learning. In the context of schools or educational institutions, academic supervision focuses on monitoring, evaluating and developing teacher performance and the teaching and learning process. This article discusses the role of academic supervision management, the basic principles underlying it and effective strategies that can be applied to improve the quality of learning. It also discusses the challenges faced in implementing academic supervision and recommendations for further improvement.